2022
DOI: 10.3390/foods11121747
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyphenol Extract from Rosa Roxburghii Fruit on Plasma Metabolome and Gut Microbiota in Type 2 Diabetic Mice

Abstract: Rosa roxburghii fruit is an underutilized functional food abundant in polyphenols. Polyphenols have been proved to have antidiabetic effects. This study investigates the effects of Rosa roxburghii fruit polyphenols extract (RPE) on plasma metabolites and gut microbiota composition in streptozotocin (STZ)- and high-fat diet- induced type 2 diabetes using metabolomics and 16S rRNA gene sequencing. The induced diabetic mice were fed with 400 mg/kg body weight RPE for 8 weeks. RPE demonstrated hypoglycemic, hypoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…( Jin et al, 2021 ). Baicalin was a natural flavonoid glycoside that attenuated intestinal oxidative stress by ameliorating the peroxidation of free radicals or enhancing the activity of antioxidant enzymes ( Wang et al, 2022 ). Notably, catechin and gallic acid, the most abundant flavonoids and phenolic acids in R. roxburghii DGs polyphenols, also made a major contribution to the phenolic antioxidant activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( Jin et al, 2021 ). Baicalin was a natural flavonoid glycoside that attenuated intestinal oxidative stress by ameliorating the peroxidation of free radicals or enhancing the activity of antioxidant enzymes ( Wang et al, 2022 ). Notably, catechin and gallic acid, the most abundant flavonoids and phenolic acids in R. roxburghii DGs polyphenols, also made a major contribution to the phenolic antioxidant activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it becomes essential to control gut microbiota homeostasis in order to maintain host health. Currently, sufficient evidences showed that diet and food components such as polyphenols can alter the gut microbial composition and promote intestinal health ( Luo et al, 2019 , Su et al, 2022 , Wang et al, 2022 , Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…RRT is rich in bioactive substances, such as vitamin C, polysaccharides, polyphenols, and SOD, often used in the research and development of functional foods [13]. Polysaccharides [17] and polyphenols [22] in RRT have been proven to have hypoglycemic effects. The previous research of our team found that RRT fruit vinegar had an ameliorating effect on dyslipidemia and other phenomena in obese mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Polydipsia, polyphagia, polyuria, and emaciation are considered typical symptoms of T2DM and their presence is among the diagnostic criteria ( 16 ). In mice, a fasting blood glucose ≥11.1 mmol/L is the diagnostic criterion for T2DM ( 22 ). T2DM can alter glycolipid metabolism in patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%